2010
DOI: 10.1371/journal.pone.0012124
|View full text |Cite
|
Sign up to set email alerts
|

Thymoquinone Induces Telomere Shortening, DNA Damage and Apoptosis in Human Glioblastoma Cells

Abstract: BackgroundA major concern of cancer chemotherapy is the side effects caused by the non-specific targeting of both normal and cancerous cells by therapeutic drugs. Much emphasis has been placed on discovering new compounds that target tumour cells more efficiently and selectively with minimal toxic effects on normal cells.Methodology/Principal FindingsThe cytotoxic effect of thymoquinone, a component derived from the plant Nigella sativa, was tested on human glioblastoma and normal cells. Our findings demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
110
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(117 citation statements)
references
References 38 publications
7
110
0
Order By: Relevance
“…In addition, these cells have several complex chromosomal rearrangements, including reciprocal and non-reciprocal translocations. 24 Although the precise mechanism is not known, it is possible that the absence of functional p53 enables cells to tolerate genomic change better than cells with p53. 25 Variability in chromosome number and genomic rearrangements are frequently associated with the presence of micronuclei.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, these cells have several complex chromosomal rearrangements, including reciprocal and non-reciprocal translocations. 24 Although the precise mechanism is not known, it is possible that the absence of functional p53 enables cells to tolerate genomic change better than cells with p53. 25 Variability in chromosome number and genomic rearrangements are frequently associated with the presence of micronuclei.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the differential expression of telomerase in cancer cells and normal somatic cells, targeting the telomere dynamics has been considered an attractive option in chemotherapy today [17][18][19]. In this regard, we have recently shown that certain natural plant products possess the ability to inhibit telomerase and subsequently induce cell death in human cancer cells [20][21][22]. To the best of our knowledge, there is no report on the effect of plumbagin on telomere dynamics in cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies show that TQ can inhibit growth of several types of cancer cells. Such anti-proliferative activities exhibited by TQ involve inhibition of cancer cell signal transduction and apoptosis, which consequently leads to reduced DNA oxidative damage (4,7,8). It also controls the Akt pathway, which means it controls the process that manages cell survival for both normal and cancer cells (18).…”
Section: Discussionmentioning
confidence: 99%
“…TQ has been demonstrated as a cytotoxic agent in several multi-drug resistant human tumor cell lines. Molecular mechanisms underlying these anticancer effects were attributed to inductions of cell cycle arrest, apoptosis, oxidative damage of cellular macromolecules, blockade of tumor angiogenesis and inhibitions in migration, invasion and metastasis of cancer cells and TQ induces DNA damage, telomere attrition by inhibiting telomerase and cell death in cancer cells (6,7). Also, the combination of TQ and conventional chemotherapeutic agents could produce greater therapeutic effect as well as enhance cytotoxic effect in tumor cells (8).…”
Section: Introductionmentioning
confidence: 99%